2020
DOI: 10.1155/2020/1418978
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on Clinicopathologic Features and Preoperative Hematology Parameters to Predict Occult Peritoneal Metastasis of Gastric Cancer: A Single-Center Retrospective Study

Abstract: Background. In patients with gastric cancer (GC), peritoneal metastasis is an indication of the end stage and often indicates a poor outcome. The diagnosis of peritoneal metastasis, especially occult peritoneal metastasis (OPM), remains a challenge for surgeons. This study was designed to explore the relationship between OPM and clinicopathological characteristics and preoperative hematological parameters in patients with GC and to develop a nomogram to predict the probability of OPM before surgery. Methods. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…After title and abstract screening, 38 studies were considered potentially eligible. After full text screening, seventeen studies were included [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The study flowchart and reasons for exclusion are shown in Figure 1 and Appendix B .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After title and abstract screening, 38 studies were considered potentially eligible. After full text screening, seventeen studies were included [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The study flowchart and reasons for exclusion are shown in Figure 1 and Appendix B .…”
Section: Resultsmentioning
confidence: 99%
“…The study flowchart and reasons for exclusion are shown in Figure 1 and Appendix B . In sixteen studies, information on incidence numbers of synchronous gastric peritoneal metastases was provided [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Risk factors for gastric peritoneal metastases were reported in four studies [ 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations